Sintesis senyawa basa Schiff dari Vanilin dan p-Toluidina menggunakan metode penggerusan - Maulidha, Isna Fifa Vilandra (Maliki Interdisciplinary Journal, 2024)
Schiff base is an aromatic organic compound composed of imine groups from the reaction of condensation of primary amines with aldehydes or ketones. The purpose of this study was to determine the results of characterization of the synthesis of Schiff base compounds produced from vanillin and p-toluidina by the grinding method. Synthetic products of vanillin and p-toluidina are tested for melting point, solubility tests or chemical properties and characterized using FTIR. The results of this experiment revealed that the use of the grinding method is very effective and efficient to use, marked by the large percentage of yield obtained, which is 96.48%. The product of the synthesis of the compound has a pale yellow solid physical form and has a melting point in the range of 113-120°C. FTIR spectra show absorption peaks associated with imine groups (-C=N) wavenumber 1624 cm-1.